Exploring the Learning Design on Learning Management System for Online Learning: A Case Study in Higher Education - Wahyuddin Rauf; Abd. Rajab; Nashruddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
E-learning has become a popular tool among 21st-century learners as the importance of lifelong learning has grown. However, most teachers find converting teaching and learning from face-to-face to online learning difficult. Current e-learning theories and practices are neither straightforward nor consistent, implying that this solution is implemented irregularly, arbitrarily, and with various degrees of success. Therefore, this study aims to discuss the Exploring the Learning Design on Learning Management System for Online Learning: A Case Study in Higher Education. This research's specific purposes are to determine how higher education teachers design their courses using LMS in an online teaching context. This research applied a qualitative approach with a case study to explore the implementation of the teaching approaches, methods, or strategies. Using purposive sampling, two lecturers who have been nominated in Online Learning System (SPADA) Award 2021 online were invited to participate as the subjects in this research. The data were gathered through interviews with open-ended questions developed by the researchers in data collection. The findings of this research show that the learning design on LMS basically can be done by stating the learning objectives. The well-defined learning objective plays vital roles since it determines the selection of activity and the learning content. Selecting learning activity, as the next phase, can be done by presenting blend materials such as text, audio, and interactive video. Providing a low-risk exercise after presenting the material is also important since it provides practice opportunities for students. The last phase is assessing the student’s performance. This activity, obviously, aims to evaluate the learning objective. So, the type of assessment, whether summative or formative, should be selected based on the learning objectives. It is important also to note that assessment may go hand-in-hand with its feedback, and the findings show that LMS enables us to apply immediate feedback for the students.